Collateral Support: Involving Parents and Schools in Treatment for Youth Anxiety. Issue 1 (2nd January 2016) - Swan, Anna J.; Kagan, Elana R.; Frank, Hannah E.; Crawford, Erika; Kendall, Philip C.
ABSTRACT: Cognitive behavioral therapy (CBT) is an empirically supported and well-established treatment for youth anxiety disorders. CBT therapists often involve parents and school staff in treatment to promote the generalization of therapeutic gains across settings. To facilitate therapist communication with those who provide collateral support, we discuss both general guidelines and specific examples of how parents and teachers can best support anxious youth by acting as coping models, labeling and validating anxious feelings, rewarding brave behavior, and reducing accommodations. We provide answers to questions commonly asked by parents (e.g., "How should I respond 'in the moment' when my child is anxious?") and by school personnel (e.g., "What is a useful role for a school in child treatment"). Handouts summarizing main concepts for parents and schools are provided.